2016
DOI: 10.1002/jssc.201600415
|View full text |Cite
|
Sign up to set email alerts
|

Determination of arsenic species in Solanum Lyratum Thunb using capillary electrophoresis with inductively coupled plasma mass spectrometry

Abstract: A simple and highly efficient interface to couple capillary electrophoresis with inductively coupled plasma mass spectrometry by a microflow polyfluoroalkoxy nebulizer and a quadruple ion deflector was developed in this study. By using this interface, six arsenic species, including arsenite, arsenate, monomethylarsonic acid, dimethylarsinic acid, arsenobetaine, and arsenocholine, were baseline-separated and determined in a single run within 11 min under the optimized separation conditions. The instrumental det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…The effects of other MAE parameters on the extraction of As species were further investigated, similar to our previous report [13]. The experimental results also revealed that the ratio of extracting solvent volume to spirulina powder mass of 300 mL/g is the best ratio (Fig.…”
Section: Optimization For the Extraction Of Arsenic Species In Spirulsupporting
confidence: 78%
See 3 more Smart Citations
“…The effects of other MAE parameters on the extraction of As species were further investigated, similar to our previous report [13]. The experimental results also revealed that the ratio of extracting solvent volume to spirulina powder mass of 300 mL/g is the best ratio (Fig.…”
Section: Optimization For the Extraction Of Arsenic Species In Spirulsupporting
confidence: 78%
“…Their RSDs (n = 5) of migration time and peak area were 0.2-1.3% and 0.8-4.8%, respectively. Their instrumental detection limit (3σ/S) calculated with counts was 5.00, 5.00, 10.0, and 10.0 ng/L, respectively, much lower than that obtained in CE-ICP-MS [13,18].…”
Section: Optimization For the Separation Of Different Arsenic Speciesmentioning
confidence: 59%
See 2 more Smart Citations
“…Inductively coupled plasma mass spectrometry (ICP‐MS), which is widely used for the determination of trace metals , possesses several inherent advantages including extremely high sensitivity for most metallic ions, wide linear dynamic range, high speed analysis, excellent mass resolution for metallic ions, and the ability to perform isotopic analysis . Therefore, the coupling of CE and ICP‐MS becomes a powerful tool for elemental speciation analysis, and has been used in the speciation analysis of some elements such as arsenic , selenium , lead , mercury , and chromium . To the best of our knowledge, the method of simultaneous analysis of Ziram and Zineb using CE–ICP‐MS has not been reported so far.…”
Section: Introductionmentioning
confidence: 99%